Preparation and Characterization of LiCoMnO4 for Lithium-Ion Battery - Mahmood, Waleed K.; Naje, Asama N. (Iraqi Journal of Science, 2022)
The LiCoMnO4 spinel compound was prepared by a sol–gel method. Structural measurements were utilized to investigate the characteristics of LCMO powder. The powder crystallizes in the space group Rd-3m, with a trigonal crystallinity structure, according to XRD analysis (hexagonal axes). SEM images showed that the crystalline grains sizes were about 200 nm - 350 nm, which provides large surface area. The sample had soft magnetic characteristics, according to hysteresis behaviour analysis in the Vibrating Sample Magnetometer (VSM). The prepared material is thought to be a candidate for the applications of energy storage in lithium-ion batteries.